Analysis of the Externalities of Coal Mining on Labor and Socio-Economics of the Community - Firmansyah, Mochammad Fikri; Hariani, Ermatry (UMSurabaya Publishing, 2025)
Coal mining activities contribute significantly to the national economy, and generate externalities that affect employment and the socio-economic conditions of communities around mining areas. This study aims to analyze the impact of positive and negative externalities from coal mining activities on employment, income, and community welfare. This research approach uses descriptive-qualitative method, with data collection through in-depth interviews, surveys, and documentation studies. The results show that coal mining activities create new employment opportunities and increase the income of local communities. However, negative impacts such as environmental damage, and changes in community social patterns are also significant concern. This study provides recommendations for more sustainable mining management, including diversification of the local econоmу. community involvement in decision-making, and increased monitoring of social and environmental impacts.